Efficacy and safety of paracetamol for spinal pain and osteoarthritis: systematic review and meta-analysis of randomised placebo controlled trials. (31st March 2015) - Machado, Gustavo C; Maher, Chris G; Ferreira, Paulo H; Pinheiro, Marina B; Lin, Chung-Wei Christine; Day, Richard O; McLachlan, Andrew J; Ferreira, Manuela L
Abstract : Objective To investigate the efficacy and safety of paracetamol (acetaminophen) in the management of spinal pain and osteoarthritis of the hip or knee. Design Systematic review and meta-analysis. Data sources Medline, Embase, AMED, CINAHL, Web of Science, LILACS, International Pharmaceutical Abstracts, and Cochrane Central Register of Controlled Trials from inception to December 2014. Eligibility criteria for selecting studies Randomised controlled trials comparing the efficacy and safety of paracetamol with placebo for spinal pain (neck or low back pain) and osteoarthritis of the hip or knee. Data extraction Two independent reviewers extracted data on pain, disability, and quality of life. Secondary outcomes were adverse effects, patient adherence, and use of rescue medication. Pain and disability scores were converted to a scale of 0 (no pain or disability) to 100 (worst possible pain or disability). We calculated weighted mean differences or risk ratios and 95% confidence intervals using a random effects model. The Cochrane Collaboration's tool was used for assessing risk of bias, and the GRADE approach was used to evaluate the quality of evidence and summarise conclusions. Results 12 reports (13 randomised trials) were included. There was "high quality" evidence that paracetamol is ineffective for reducing pain intensity (weighted mean difference −0.5, 95% confidence interval −2.9 to 1.9) and disability (0.4, −1.7 to 2.5) or improving quality of life (0.4, −0.9 to 1.7) in the short term in people with low back pain. For hip or knee osteoarthritis there was "high quality" evidence that paracetamol provides a significant, although not clinically important, effect on pain (−3.7, −5.5 to −1.9) and disability (−2.9, −4.9 to −0.9) in the short term. The number of patients reporting any adverse event (risk ratio 1.0, 95% confidence interval 0.9 to 1.1), any serious adverse event (1.2, 0.7 to 2.1), or withdrawn from the study because of adverse events (1.2, 0.9 to 1.5) was similar in the paracetamol and placebo groups. Patient adherence to treatment (1.0, 0.9 to 1.1) and use of rescue medication (0.7, 0.4 to 1.3) was also similar between groups. "High quality" evidence showed that patients taking paracetamol are nearly four times more likely to have abnormal results on liver function tests (3.8, 1.9 to 7.4), but the clinical importance of this effect is uncertain. Conclusions Paracetamol is ineffective in the treatment of low back pain and provides minimal short term benefit for people with osteoarthritis. These results support the reconsideration of recommendations to use paracetamol for patients with low back pain and osteoarthritis of the hip or knee in clinical practice guidelines. Systematic review registration PROSPERO registration number CRD42013006367.